Cardiometabolic Multimorbidity Associated with Moderate and Severe Disabilities: Results from the Study on Global AGEing and Adult Health (SAGE) Wave 2 in Ghana and South Africa - Peter Otieno; Gershim Asiki; Justice Moses K. Aheto; Calistus Wilunda; Richard E. Sanya; Welcome Wami; Daniel Mwanga; Charles Agyemang (Global Heart, 2023)
Background: Integrated management of cardiometabolic diseases is crucial in improving the quality of life of older persons. The objective of the study was to identify clusters of cardiometabolic multimorbidity associated with moderate and severe disabilities in Ghana and South Africa. Methods: Data were from the World Health Organization (WHO) study on global AGEing and adult health (SAGE) Wave-2 (2015) conducted in Ghana and South Africa. We analysed the clustering of cardiometabolic diseases including angina, stroke, diabetes, obesity, and hypertension with unrelated conditions such as asthma, chronic lung disease, arthritis, cataracts, and depression. The WHO Disability Assessment Instrument version 2.0 was used to assess functional disability. We used latent class analysis to calculate the multimorbidity classes and disability severity levels. Ordinal logistic regression was used to identify the clusters of multimorbidity associated with moderate and severe disabilities. Results: Data from 4,190 adults aged over 50 years were analysed. The prevalence of moderate and severe disabilities was 27.0% and 8.9% respectively. Four latent classes of multimorbidity were identified. These included a relatively healthy group with minimal cardiometabolic multimorbidity (63.5%), general and abdominal obesity (20.5%), hypertension, abdominal obesity, diabetes, cataracts, and arthritis (10.0%), and angina, chronic lung disease, asthma, and depression (6.0%). Compared to the participants with minimal cardiometabolic multimorbidity, the odds of moderate and severe disabilities were higher among participants with multimorbidity comprising hypertension, abdominal obesity, diabetes, cataract and arthritis [aOR = 3.0; 95% CI 1.6 to 5.6], and those with angina, chronic lung disease, asthma and depression [aOR = 2.7; 95% CI 1.6 to 4.5]. Conclusions: Cardiometabolic diseases among older persons in Ghana and South Africa cluster in distinct multimorbidity patterns that are significant predictors of functional disabilities. This evidence may be useful for defining disability prevention strategies and long-term care for older persons living with or at risk of cardiometabolic multimorbidity in sub-Saharan Africa.